Color vision and the railways: Part 1. The railway LED lantern test - Dain, Stephen J; Casolin, Armand; Long, Jennifer; Hilmi, Mohd Radzi (Wolters Kluwer Health, 2015)
Purpose. Lantern tests and practical tests are often used in the assessment of prospective railway employees. The lantern tests rarely embody the actual colors used in signaling on the railways. Practical tests have a number of problems, most notably consistency of application and practicability. This work was carried out to provide the Railway LED Lantern Test (RLLT) as a validated method of assessing the color vision of railway workers. Methods. The RLLT, a simulated practical test using the same LEDs (light-emitting diodes) as are used in modern railway signals, was developed. It was tested on 46 color visionYnormal (CVN) and 37 color visionYdeficient (CVD) subjects. A modified prototype was then tested on 106 CVN subjects. Results. All 106 CVN subjects and most mildly affected CVD subjects passed the modified lantern at 3 m. At 6 m, 1 of the 106 normal color vision subjects failed by missing a single red light. All the CVD subjects failed. The RLLT carried out at 3 m allowed mildly affected CVD subjects to pass and demonstrate adequate color vision for the less demanding railway tasks. Carried out at 6 m, it essentially reinforced normal color vision as the standard. Conclusions. TheRLLTisasimplyadministeredtestthathasadirectlinktotheactualvisualtaskoftherailworker.TheRLLT lantern has been adopted as an approved test in the Australian National Standard for Health Assessment of Rail Safety Workers in place of a practical test. It has the potential to be a valid part of any railway color vision standard.